Théorie comptable de la monnaie et de la finance - Maxime Izoulet (Revue de la Régulation)
This phd dissertation aims at demonstrating that the invention of double entry bookkeeping in Italy in the early 14th century, paved the way to modern credit money. Since it allows a new definition of value, both complete and efficient, double entry bookkeeping has led to the development of a feedback loop between the circulation of claims and profit growth, whose meaning has been defined by double entry bookkeeping itself. As it developed over time in relation to the trade of commodities, this system of credit money, which was initially pegged to official currency, has then become autonomous during conflicts, in different countries, when its convertibility with the official currency was suspended. From this interpretation of the history of money, drawing on an accounting theory of value, this thesis aims at demonstrating that contemporary financial markets work as a substitution for money, by developing autonomously during liquidity shortages, and maintaining a negative causal relationship with inflation, as shown by many econometric studies.